Enhancing the bioaccessibility of L-Citrulline using chitosan-coated nanoliposomes: Physicochemical properties and release kinetics in simulated gastrointestinal conditions - Mahsa Mohseni; Mohammad Mousavi; Hossein Kiani; Mina Homayoonfal; Amir Khademi (Journal of Agriculture and Food Research)
L-Citrulline, a non-protein amino acid with significant roles in mammalian metabolism and therapeutic potential, was encapsulated in nanoliposomes and chitosan-coated nanoliposomes to improve its stability and bioaccessibility. The purpose of this study was to develop and characterize these encapsulation systems, evaluate their release behavior under simulated gastrointestinal conditions, and assess their potential for oral delivery of L-Citrulline. These systems were analyzed for their physicochemical properties, including particle size, zeta potential, and encapsulation efficiency, as well as their release patterns. Nanoliposomes exhibited particle sizes ranging from 114 to 221 nm with a narrow size distribution (PDI: 0.2–0.29), indicating uniformity and stability. The application of a chitosan coating significantly enhanced particle stability, shifting the zeta potential from −65 mV to +64 mV. Encapsulation efficiency increased from 53.7 % ± 1.3–73.4 % ± 0.8 with chitosan coating, demonstrating the superior retention capability of the coated nanoliposomes. The release profile showed controlled release behavior, with 8.99 % of L-Citrulline released in the gastric phase and 26.34 % released in the intestinal phase within the first hour. Chitosan-coated nanoliposomes exhibited a slower and more sustained release compared to uncoated nanoliposomes, which released L-Citrulline more rapidly. The results highlight that coating nanoliposomes with chitosan not only enhanced stability but also modulated the release behavior, ensuring prolonged retention and improved bioavailability in gastrointestinal environments. In conclusion, this study demonstrated that chitosan-coated nanoliposomes are a promising and innovative delivery system for bioactive compounds like L-Citrulline, offering improved stability, encapsulation efficiency, and controlled release profiles, making them suitable for functional food and pharmaceutical applications.